A Neutral η5‐Aminoborole Complex of Germanium(II). Issue 40 (7th September 2018) - Tholen, Patrik; Dong, Zhaowen; Schmidtmann, Marc; Albers, Lena; Müller, Thomas
Abstract: The synthesis of two η 5 ‐aminoborole complexes of germanium(II) from the reaction of a germole dianion with aminoboron dichlorides is reported. This reaction constitutes a remarkable example of a germole‐to‐borole transformation. The two aminoborole complexes of germanium(II) were fully characterized by multinuclear NMR spectroscopy, IR spectroscopy, HRMS, and, in one case, by X‐ray crystallography. The results of quantum‐mechanical calculations favor the electronic structure of a half‐sandwich complex of Ge II over an ionic representation with a germanium dication stabilized by an aromatic aminoborole dianion. Abstract : Germole to borole : The synthesis of η 5 ‐aminoborole complexes of germanium(II) from the reaction of a germole dianion with aminoboron dichlorides is reported. This process constitutes a remarkable example of a germole‐to‐borole transformation.